PROGRAM PENDAMPINGAN TEKNIS BAGI MASYARAKAT UNTUK MENDUKUNG KELAYAKAN BANGUNAN RUMAH TINGGAL BERBASIS LOKALITAS DI KOTA BONTANG KALIMANTAN TIMUR - Prasetyo, Prasetyo; Dimas Bintang Mudrajad; Ayesha Amiranti Putri Masagung; Sri Wahyuni; Toni Sugiarto; Adhe Fauzul Richani; Nadia Hasna (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The technical assistance program for communities plays a crucial role in ensuring the feasibility of residential buildings, particularly in rapidly developing areas such as Bontang City, East Kalimantan. This article examines the implementation of a community assistance program designed to enhance the capacity of local residents in understanding and complying with technical documentation and building feasibility standards based on local context. The program is grounded in Government Regulation No. 16 of 2021, which implements Law No. 28 of 2002 on Buildings, governing technical planning, construction execution, and building feasibility certification. The locality-based approach integrates local wisdom, environmental characteristics, and the specific needs of the community into building technical planning and implementation. The methods employed include community needs analysis, technical training, and assistance in preparing technical documents such as working drawings, cost estimates (RAB), and building feasibility certification. The program results indicate an improvement in the community's understanding of applicable technical regulations and administrative procedures, as well as enhanced building quality that meets safety and comfort standards. Additionally, the program successfully encouraged active community participation in the construction process and fostered collaboration between local governments, academics, and local residents. This article concludes that a locality-based approach not only accelerates the fulfillment of building feasibility requirements but also strengthens sustainable development in Bontang City. Recommendations for program development include expanding implementation scope and integrating technology to support more efficient technical assistance processes